Implementasi Kebijakan Pendidikan Umum dan Pendidikan Karakter di Perguruan Tinggi - Nanggala, Agil; Sundawa, Dadang (Jurnal Ilmiah Pendidikan Pancasila dan Kewarganegaraan, 2023)
This study aims to analyze the implementation of general education and character policies in universities and the urgency of establishing general education and character study programs for universities. This study uses a qualitative approach with literature study techniques. The implementation of general education and character policies in higher education can be carried out by the technical implementation unit of compulsory curriculum courses and carried out in the form of study programs that specifically overshadow general education and character. The urgency of establishing a general education and character study program for universities is related to strengthening the superior character of students as well as strengthening institutional identity, especially for educational institutions of education personnel that have the status of state universities as legal entities.